Formation of amyloid in encapsulated human pancreatic and human stem cell‐generated beta cell implants. Issue 6 (6th December 2020) - Van Hulle, Freya; De Groot, Kaat; Stangé, Geert; Suenens, Krista; De Mesmaeker, Ines; De Paep, Diedert L.; Ling, Zhidong; Hilbrands, Robert; Gillard, Pieter; Keymeulen, Bart; Kroon, Evert; Westermark, Gunilla T.; et al.
Abstract: Detection of amyloid in intraportal islet implants of type 1 diabetes patients has been proposed as cause in their functional decline. The present study uses cultured adult human islets devoid of amyloid to examine conditions of its formation. After intraportal injection in patients, amyloid deposits <15 µm diameter were identified in 5%–12% of beta cell containing aggregates, 3–76 months posttransplant. Such deposits also formed in glucose‐controlling islet implants in the kidney of diabetic mice but not in failing implants. Alginate‐encapsulated islets formed amyloid during culture when functional, and in all intraperitoneal implants that corrected diabetes in mice, exhibiting larger sizes than in functioning nonencapsulated implants. After intraperitoneal injection in a patient, retrieved single capsules presented amyloid near living beta cells, whereas no amyloid occurred in clustered capsules with dead cells. Amyloid was also demonstrated in functional human stem cell‐generated beta cell implants in subcutaneous devices of mice. Deposits up to 35 µm diameter were localized in beta cell‐enriched regions and related to an elevated IAPP over insulin ratio in the newly generated beta cells. Amyloid in device‐encapsulated human stem cell‐generated beta cell implants marks the formation of a functional beta cell mass but also an imbalance between its activated state and its microenvironment. Abstract : Formation of amyloid in device‐encapsulated implants of human stem cell–derived pancreatic endoderm marks the generation of functionally activated beta cell clusters near sites where the microenvironment favors aggregation of released islet amyloid polypeptide.